Xixin Decoction’s novel mechanism for alleviating Alzheimer’s disease cognitive dysfunction by modulating amyloid-β transport across the blood–brain barrier to reduce neuroinflammation - Yang, Chaokai; Zhao, Enlong; Zhang, Hu; Duan, Liqi; Han, Xinyue; Ding, Hongli; Cheng, Yan; Wang, Dengkun; Lei, Xiaojing; Diwu, Yongchang (Frontiers in Pharmacology, 2025)
PurposeXixin Decoction (XXD) is a classical formula that has been used to effectively treat dementia for over 300 years. Modern clinical studies have demonstrated its significant therapeutic effects in treating Alzheimer’s disease (AD) without notable adverse reactions. Nevertheless, the specific mechanisms underlying its efficacy remain to be elucidated. This investigation sought to elucidate XXD’s impact on various aspects of AD pathology, including blood-brain barrier (BBB) impairment, neuroinflammatory processes, and amyloid-β (Aβ) deposition, as well as the molecular pathways involved in these effects.MethodsIn vitro experiments were conducted using hCMEC/D3 and HBVP cell coculture to establish an in vitro blood-brain barrier (BBB) model. BBB damage was induced in this model by 24-h exposure to 1 μg/mL lipopolysaccharide (LPS). After 24, 48, and 72 h of treatment with 10% XXD-medicated serum, the effects of XXD were assessed through Western blotting, RT-PCR, and immunofluorescence techniques. In vivo, SAMP8 mice were administered various doses of XXD via gavage for 8 weeks, including high-dose XXD group (H-XXD) at 5.07 g kg-1·d-1, medium-dose XXD group (M-XXD) at 2.535 g kg-1·d-1, and low-dose XXD group (L-XXD) at 1.2675 g kg-1·d-1. Cognitive function was subsequently evaluated using the Morris water maze test. BBB integrity was evaluated using Evans blue staining, and protein expression levels were analyzed via ELISA, Western blotting, and immunofluorescence.ResultsIn vitro experiments revealed that XXD-containing serum, when cultured for 24, 48, and 72 h, could upregulate the expression of P-gp mRNA and protein, downregulate CB1 protein expression, and upregulate CB2 and Mfsd2a protein expression. In vivo studies demonstrated that XXD improved spatial learning and memory abilities in SAMP8 mice, reduced the amount of Evans blue extravasation in brain tissues, modulated the BBB-associated P-gp/ECS axis, RAGE/LRP1 receptor system, as well as MRP2 and Mfsd2a proteins, and decreased the accumulation of Aβ in the brains of SAMP8 mice. Additionally, XXD upregulated the expression of TREM2, downregulated IBA1, TLR1, TLR2, and CMPK2 expression, and reduced the levels of pro-inflammatory factors NLRP3, NF-κB p65, COX-2, TNF-α, and IL-1β in the hippocampal tissues.ConclusionXXD may exert its effects by regulating the P-gp/ECS axis, the RAGE/LRP1 receptor system, and the expression of MRP2 and Mfsd2a proteins, thereby modulating the transport function of the BBB to expedite the clearance of Aβ, reduce cerebral Aβ accumulation, and consequently inhibit the activation of microglia induced by Aβ aggregation. This process may suppress the activation of the CMPK2/NLRP3 and TLRs/NF-κB pathways, diminish the production of inflammatory cytokines and chemokines, alleviate neuroinflammation associated with microglia in the brain of AD, and ultimately improve AD pathology.